English Language Education in Indonesia: A Literature Review of Teaching Methods, Curriculum, and Challenges - Khalisa, Lia (Global Education Journal, 2025)
English language education in Indonesia has developed rapidly, in line with globalization and the increasing need to communicate in an international language. This article aims to examine the various English language teaching methods used in Indonesia, identify the implemented curriculum, and review the challenges faced in teaching English at the formal education level. This article uses a literature review approach to analyze relevant literature on methods, curriculum, and the challenges faced by teachers and students in English language education. The review results indicate that despite the implementation of modern teaching methods, significant challenges related to curriculum implementation and the use of technology remain, affecting the quality of English language teaching in Indonesia. Therefore, this article recommends the need for improved teacher training and strengthening technical support and resources throughout Indonesia.